1988
DOI: 10.1002/mpo.2950160308
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of neuroblastoma metastasis in bone marrow with a panel of monoclonal antibodies

Abstract: Neuroblastoma, along with rhabdomyosarcoma, Ewing's sarcoma, and acute lymphoblastic leukemia/lymphoma, is one of the small, round-cell tumors of childhood. All of these malignancies show a propensity to metastasize to bone marrow. Occasionally when the clinical picture is unclear and the tumor is particularly anaplastic, it can be difficult to arrive at a diagnosis by conventional histological and biochemical procedures. In the present study, a panel of nine monoclonal antibodies was used to undertake a detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Despite this, early studies in neuroblastoma patients already showed BM infiltration by CD45 − /CD56 + tumor cells, in the absence of proteins denoting hematopoietic commitment [29], [33]. Because of the relatively high frequency of metastatic BM involvement in neuroblastoma, this is by far the non-hematopoietic pediatric tumor mostly studied by MFC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, early studies in neuroblastoma patients already showed BM infiltration by CD45 − /CD56 + tumor cells, in the absence of proteins denoting hematopoietic commitment [29], [33]. Because of the relatively high frequency of metastatic BM involvement in neuroblastoma, this is by far the non-hematopoietic pediatric tumor mostly studied by MFC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, usage of flow cytometry in pediatric solid tumors has been almost restricted to the evaluation of tumor cell DNA contents in both paraffin-embedded and frozen tissue specimens, in combination or not with simultaneous staining for one or a few phenotypic markers [19][24]. Consequently, while immunophenotypic studies are routinely applied in most pediatric lymphomas for the differential diagnosis between B- and T-cell precursor lymphoblastic lymphomas and Burkitt lymphoma 2528, few studies have been reported so far, in which MFC is systematically applied to the study of the phenotypic characteristics of pediatric solid tumors [29][31]. In addition, the few reported studies have mainly focused on descriptive analyses of the staining patterns for one or a few markers, usually in a single diagnostic subtype of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Many NB-associated antigens are inappropriate for detection of MD and MRD because of their heterogeneous expression in individual tumours or co-expression by normal cells (Sugimoto et al, 1988). In contrast, disialoganglioside G D2 is reported to be homogeneously and strongly expressed on neuroblastic tumours (Schulz et al, 1984;Cheung et al, 1985;Shochat et al, 1988), but not on normal haematopoietic cells (Cheung et al, 1986) and is therefore regarded as ideal for specific and sensitive detection of MD and MRD by IC and FC (Warzynski et al, 2002, Swerts et al, 2004.…”
Section: Antigensmentioning
confidence: 99%
“…The monoclonal antibodies UJ-13A and UJ-127-1 1 were used to detect neuroblasts in the bone marrow. These antibodies were kindly given to us by Dr. Kemshead [9,14]. These monoclonal antibodies bind specifically to neuroblastoma cells but not to normal BM cells and to leukemic cells.…”
Section: Methodsmentioning
confidence: 99%